PENGARUH MODEL PEMBELAJARAN ROLE PLAYING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS NEGOSIASI SISWA KELAS X MAN 2 KOTA PADANG - Puteri Adely, Nafla; R, Syahrul; Abdurrahman; Syafrina, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the effect of using a role-playing learning model assisted by audiovisual media on students’ negotiation text writing skills at grade X of MAN 2 Kota Padang. This research employed a quantitative approach with a pre-experimental method using a one-group pretest-posttest design. The population consisted of all grade X students of MAN 2 Kota Padang totaling 443 students, while the sample consisted of 32 students selected through purposive sampling technique. The research instrument was a performance test in writing negotiation texts, assessed based on content, text structure, language features, and spelling. The data were analyzed using descriptive and inferential statistics, particularly paired sample t-test. The results showed that the mean score increased from 73.14 in the pretest to 79.00 in the posttest. The hypothesis testing indicated that there was a significant effect of using the role-playing learning model assisted by audiovisual media on students’ negotiation text writing skills. Therefore, this learning model is effective in improving students’ writing skills.